The Quality of the Maternity Triage Process: a Qualitative Study - Rashidi-Fakari, Farzaneh (Adv J Emerg Med, 2019)
INTRODUCTION: There is no consensus on what the bases and criteria are for the dynamic process of maternity triage. Properly performing the maternity triage process requires reliable data to ensure the correct implementation of this process and the identification of existing deficiencies, and find strategies to modify, improve and enhance the quality of this process. OBJECTIVE: The present study was conducted to explain the quality of the maternity triage process. METHODS: The present qualitative study performed a directed content analysis on 19 maternity triage service providers and key informants selected through purposive sampling. The data were collected through semi-structured interviews in 2018 and analyzed using directed content analysis based on the Donabedian’s model. The accuracy and rigor of the qualitative data were then investigated and confirmed. RESULTS: The participants identified the most important factors affecting the quality of the services provided in maternity triage as two categories of measures and care, and interactions and communication. The category of measures and care included two subcategories of examinations and obtaining a medical history. CONCLUSION: The present study comprehensively identified different dimensions of the quality of maternity triage services at different levels. The participants identified the quality of the maternity triage process as a multi-dimensional and important concept. Different dimensions of the maternity triage process are recommended that be addressed when designing and implementing maternity triage guidelines and instructions so as to maintain the quality of this process and satisfy their needs.